METODE GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBANTU SISWA TUNANETRA (GANGGUAN PADA PENGLIHATAN) DALAM BELAJAR - Warasi, Sepniwati; Gulo, Atirina; Liunokas, Novi; Tatubeket, Ela Meronisa R.; Hasibuan, Nelson (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
The purpose of this study is to find out and provide appropriate teaching methods for Christian Religious Education (PAK) teachers to help visually impaired students in learning. Because there are still Christian religious education teachers in teaching the visually impaired only use conventional methods (lectures) which are monotonous and less interesting. As a result, students often feel bored and have difficulty understanding the learning material. For this reason, this research uses a qualitative method with a literature research approach. Data was collected by reviewing various literature, articles, books, and related sources of information. The results show that Christian Religious Education teachers can use several teaching methods that are suitable for the characteristics of visually impaired students, such as the lecture method, question and answer method, discussion method, and drill method. In addition, Christian Religious Education teachers must give special attention, guide, and motivate blind students to help them learn. The conclusion of this research is that Christian Religious Education teachers must be able to apply a variety of appropriate and interesting teaching methods in an innovative, creative, and versatile manner to optimize the learning experience of blind students, making learning more effective and enjoyable. Appropriate teaching methods and supportive approaches significantly improve students' engagement and understanding of the teaching materials.